Role of Circular RNAs in the Regulation of Immune Cells in Response to Cancer Therapies - Carlos-Reyes, Ángeles; Romero-Garcia, Susana; Contreras-Sanzón, Estefania; Ruiz, Víctor; Prado-Garcia, Heriberto (Frontiers in Genetics, 2022)
Circular RNAs (CircRNAs) are a class of small endogenous noncoding RNA that are formed by means of either the spliceosome or lariat-type splicing. CircRNAs have multiple regulatory functions and have been detected in different cell types, like normal, tumor and immune cells. CircRNAs have been suggested to regulate T cell functions in response to cancer. CircRNAs can enter into T cells and promote the expression of molecules that either trigger antitumoral responses or promote suppression and the consequent evasion to the immune response. Additionally, circRNAs may promote tumor progression and resistance to anticancer treatment in different types of neoplasias. In this minireview we discuss the impact of circRNAs and its function in the regulation of the T-cells in immune response caused by cancer therapies.